(3EOGQI GdGfJGL hGdYedjGJ (B:s (3eONd cej (B/s - (3GdYHO, MdGd GHQGgjes ((3GdEScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2002)
(3GdGfJGL hGdGfJGLjI,GdJfHD HGdWdH,CSGdjH LOhdI GdGfJGL aj GdGLd GdbUjQ,GdJNWjW GdGLeGdj,GdHQeLI GdNWjI,GdMd GdHjGfj,GdJNWjW h eJGHYI GdeTQhYGJ,feGPL GdeMGcGI,fXQjI Uaha GdGfTWGQs
(3GdeQGLY U(B.327s
Keywords: (3GdEfJGLs; (3GdGfJGLjIs; (3GdWdHs